2020
DOI: 10.7831/ras.8.0_158
|View full text |Cite
|
Sign up to set email alerts
|

Microbial α-Amylases in the Industrial Extremozymes

Abstract: Amylase is part of an enzyme group that hydrolyzes starch, and many amylases are commercially used for starch hydrolysis in several industrial processes. For industrial applications of amylases, the reaction conditions for starch hydrolysis also differ depending on each industrial use. There are various microbial amylases that have been isolated and developed, which have suitable enzymatic properties for each application. Especially, some microbial amylases included in "extremozymes" have been widely applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Similar results were recorded in the mesophilic bacterial strain studied by Poddar et al (2012).The findings of the present study indicated that the enzyme produced was cold active but producer strain was mesophilic. According to Putri and Nakagawa (2020), several mesophilic bacterial strains, mainly Bacillus species were known that produce thermophilic alphaamylases. The growth and enzyme production decreased significantly above 40°C (Samanta et al, 2013), which indicated the mesophilic character of the strain.…”
Section: Determination Of Amylolytic Naturementioning
confidence: 99%
“…Similar results were recorded in the mesophilic bacterial strain studied by Poddar et al (2012).The findings of the present study indicated that the enzyme produced was cold active but producer strain was mesophilic. According to Putri and Nakagawa (2020), several mesophilic bacterial strains, mainly Bacillus species were known that produce thermophilic alphaamylases. The growth and enzyme production decreased significantly above 40°C (Samanta et al, 2013), which indicated the mesophilic character of the strain.…”
Section: Determination Of Amylolytic Naturementioning
confidence: 99%
“…The plants and microorganisms producing extracellular isoamylase (1,6‐alpha‐D‐glucan‐glycohydrolase, EC 3.2.1.68) is involved in the degradation of α‐1,6‐glucosidic linkage at the side chain of starch polysaccharide (Zarina Putri & Nakagawa, 2020). The food ingredients such as maltose, glucose sirup, maltitol, trehalose, and cyclodextrin are normally produced by the action of isoamylase on starch molecules.…”
Section: Classification Of Amylasesmentioning
confidence: 99%
“…Due to diverse genetic makeup, the microorganisms have been adapted to cope with extreme conditions such as high temperature, pressure, salinity, acidity, and basicity. So, they produce α‐amylases which are psychrophilic (work at ≤24°C), mesophilic (work at 24–40°C), thermophilic (work at ≥50°C), alkaliphilic, acidophilic, and halophilic in nature (Zarina Putri & Nakagawa, 2020). The α‐amylases from bacterial B. licheniformis, Thermomyces lanuginosus, Pyrococcus , and Thermococcus strains are some well‐known examples of thermostable enzymes (Ghosh et al, 2020).…”
Section: Sources Of α‐Amylasementioning
confidence: 99%
“…The plants and microorganisms producing extracellular isoamylase (1,6-alpha-D-glucan-glycohydrolase, EC 3.2.1.68) is involved in the degradation of α-1,6-glucosidic linkage at the side chain of starch polysaccharide (Zarina Putri & Nakagawa, 2020). The food ingredients such as maltose, glucose sirup, maltitol, trehalose, and cyclodextrin are normally produced by the action of isoamylase on starch molecules.…”
Section: Isoamylasementioning
confidence: 99%
“…Due to diverse genetic makeup, the microorganisms have been adapted to cope with extreme conditions such as high temperature, pressure, salinity, acidity, and basicity. So, they produce α-amylases which are psychrophilic (work at ≤24°C), mesophilic (work at 24-40°C), thermophilic (work at ≥50°C), alkaliphilic, acidophilic, and halophilic in nature (Zarina Putri & Nakagawa, 2020). The α-amylases from bacterial B. licheniformis, Thermomyces lanuginosus, Pyrococcus, and Thermococcus strains are some…”
Section: Archaeal α-Amylasesmentioning
confidence: 99%